Outcomes of Corneal Topography among Progressive Keratoconus Patients 12 months following Corneal Collagen Cross-Linking - AlQahtani BS (Dove Medical Press, 2021)
Bader S AlQahtani,1– 3 Saeed Alshahrani,1,2 Waleed W Khayyat,4,5 Maram EA Abdalla-Elsayed,6 Abdullah A Altalhi,3,4 Amjad A Saifaldein,7 Mohammed A Taha1,2 1College of Medicine, King Saud Bin Abdulaziz University for Health Sciences, Riyadh, Saudi Arabia; 2King Abdullah International Medical Research Center, Riyadh, Saudi Arabia; 3Department of Ophthalmology, King Abdulaziz Medical City, Ministry of National Guard Health Affairs, Jeddah, Saudi Arabia; 4College of Medicine, King Saud Bin Abdulaziz University for Health Sciences, Jeddah, Saudi Arabia; 5King Khalid Eye Specialist Hospital, Riyadh, Saudi Arabia; 6Department of Ophthalmology, Jeddah Eye Hospital, Jeddah, Saudi Arabia; 7Department of Ophthalmology, College of Medicine, King Saud University, Riyadh, Saudi ArabiaCorrespondence: Saeed AlshahraniCollege of Medicine, King Saud Bin Abdulaziz University for Health Sciences, Ar Rimayah, Riyadh 11481, Saudi ArabiaTel +966-53-089- 5550Email saeedalshahrani158@gmail.comPurpose: This study aimed to assess the overall and specific topographic changes among patients who underwent corneal collagen cross-linking (CXL) due to progressive keratoconus.Methods: This retrospective case series study was conducted at a single-arm hospital in King Abdulaziz Medical City, Riyadh. All progressive keratoconus patients who underwent CXL between January 2017 and December 2018 were included consecutively. The epi-off crosslinking technique (Dresden protocol) was applied in all patients. The topographic values were measured preoperatively and 12 months postoperatively. Patients with a history of a previous corneal procedure, corneal trauma, or any corneal scarring were excluded.Results: Among our population (29 eyes of 24 patients), 58.6% of eyes were for male patients, and the mean age of the population was 27.76 ± 4.21 years. Based on the topography results, the mean values of corneal thickness at central 3 mm decreased from 473.45 ± 38 μm to 465.72 ± 41.78 μm following CXL (Z = − 1.93, 95% confidence interval [CI] = 0.048– 0.057, p= 0.053). Clinically significant astigmatism measurements were present in 28 (96.6%) eyes before CXL compared to 26 (89.7%) eyes after CXL. The mean values of astigmatism among the patients were 3.37 ± 2.25 diopters before and 3.67 ± 2.61 diopters after CXL (Z = − 1696, 95% confidence interval [CI] = 0.085– 0.096, p = 0.09). After CXL, the mean values of the front elevation at the apex changed from 33.90 ± 20.13 μm to 36.10 ± 21.09 μm (Z = − 2.792, 95% [CI] = 0.003– 0.006, p = 0.005). The mean values of the back elevation at the apex changed from 68.4 ± 35.66 μm to 69.90 ± 35.89 μm (Z = − 0.934, 95% CI = 0.343– 0.366, p = 0.35).Conclusion: The topographic corneal parameters improved significantly in the patients with corneal ectasia after CXL. These results revealed the safety and efficacy of CXL in stabilizing keratoconus progression among Saudi patients at 1 year of follow-up.Keywords: corneal collagen cross-linking, keratoconus, topography, corneal ectasia